Artificial Intelligence Theory, Models, and Applications - Kaliraj, P.; Devi, T. (Milton : Auerbach Publishers, Incorporated, 2021)
This book examines the fundamentals and technologies of Artificial Intelligence (AI) and describestheir tools, challenges, and issues. It also explains relevant theory as well as industrial applications in various domains, such as healthcare, economics, education, product development, agriculture, human resource management, environmental management, and marketing. The book is a boon to students, software developers, teachers, members of boards of studies, and researchers who need a reference resource on artificial intelligence and its applications and is primarily intended for use in courses offered by higher education institutions that strive to equip their graduates with Industry 4.0 skills. FEATURES: Gender disparity in the enterprises involved in the development of AI-based software development as well as solutions to eradicate such gender bias in the AI world A general framework for AI in environmental management, smart farming, e-waste management, and smart energy optimization The potential and application of AI in medical imaging as well as the challenges of AI in precision medicine AI's role in the diagnosis of various diseases, such as cancer and diabetes The role of machine learning models in product development and statistically monitoring product quality Machine learning to make robust and effective economic policy decisions Machine learning and data mining approaches to provide better video indexing mechanisms resulting in better searchable results ABOUT THE EDITORS: Prof. Dr. P. Kaliraj is Vice Chancellor at Bharathiar University, Coimbatore, India. Prof. Dr. T. Devi is Professor and Head of the Department of Computer Applications, Bharathiar University, Coimbatore, India.
3.3 AI for Water Preservation -- Smart Water Management -- 3.3.1 Current Challenges -- 3.3.2 Potential AI Applications -- 3.3.3 Sample Case Study -- 3.4 AI for Better Agriculture -- Smart Farming -- 3.4.1 Current Challenges -- 3.4.2 Potential AI Applications -- 3.4.3 Sample Case Study -- 3.5 AI for Better e-Waste Management -- Smart Monitoring/Control -- 3.5.1 Current Challenges -- 3.5.2 Potential AI Applications -- 3.5.3 Sample Case Study -- 3.6 AI for Climate Control -- Smart Energy Optimization -- 3.6.1 Current Challenges -- 3.6.2 Potential AI Applications -- 3.6.3 Sample Case Study
Description based upon print version of record.
3.7 Risks and Rewards of AI in Environmental Management.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Mathematical models; COMPUTERS / Artificial Intelligence; COMPUTERS / Neural Networks; COMPUTERS / Bioinformatics